Estudo paramétrico de um sistema fotovoltaico off-grid para operação de um tubo de vórtice - Modolo, Angelo Bezerra (2019)
Vortex tubes are passive devices which split a compressed air inlet into a cold and a hot outlets without work input or movable parts. Vortex tube has advantages over traditional vapor compression refrigeration cycles, which use refrigerants. These fluids must present good thermodynamic properties, but often present undesirable characteristics as global warming potential, flammability and/or toxicity. Therefore, present work proposes supplying compressed air to the vortex tube through a compressor connected to a photovoltaic system, made of a photovoltaic modules array, a battery pack, charge controller, variable frequency drive, compressor and compressed air storage tank. Meteorological data from one operation day of an experimental pumping system were used to model and simulate the proposed system components. Altogether, 168 distinct photovoltaic system setups were assessed by changing photovoltaic panels capacity, battery capacity and compressor power in order to calculate compressor maximum operation time in a day. The different setups were tested in three distinct initial battery state of charge conditions. Meanwhile, the mechanical system was studied at nine different setups with different values for compressor power and tank volume for three distinct initial tank pressure conditions. It has been observed that the interval the photovoltaic system can uphold compressor operation is strongly related to battery capacity and control strategy. Big discharged battery packs demands long charging times and can cause exclusive day-long charging, without any compressor operation. On the other hand, when initially fully charged, for a minimum value of capacity the battery packs, it can uphold day-long compressor operation for some system setups. Therefore, most of setups present optimal battery pack capacity values ranging from 360 Ah to 1050 Ah. At last, it was observed that solely the 15 hp compressor is able to uphold uninterrupted vortex tube operation.